University faculty perceptions about accommodations for students with learning disabilities. Issue 4 (21st March 2022) - Khouri, Marlyn; Lipka, Orly; Shecter-Lerner, Michal
ABSTRACT: Researchers have identified accommodations as important determinants of academic performance among students with learning disabilities (LD) in post-secondary education. The purpose of the current study was to examine the willingness of university faculty members in one northern university in Israel to provide accommodations for students with LD, using quantitative and qualitative measures. The 56 faculty members who participated in the study generally had positive attitudes towards accommodations for students with LD. Differences in willingness to provide technological accommodations were found between the Arabic- and Hebrew-speaking faculty members . When asked how they could support students with LD, faculty members mentioned outside sources of support, such as accommodations and referral to other assistance providers, but also saw themselves as agents of support through personal assistance and modified teaching methods. Interestingly, faculty members did not refer solely to academic support, but also to emotional support and empathy. Practical and theoretical implications are discussed.